Study on the genetic mechanism of high-temperature geothermal system and its engineering impact in the Woka graben, Tibet - Zhang, Wen; Xu, Mo; Wu, Sen (Frontiers in Earth Science, 2022)
Geothermal resource has become the significant constitution of renewable and clean energies in the world. This study focuses on the genetic mechanism of high-temperature geothermal system and its engineering impact in the Woka graben, southern Tibet by hydrochemical and isotopic analyses. The hydrochemical types are mainly SO4-Na type, SO4-Cl-Na type, HCO3-SO4-Na type. Geothermal water is characterized as medium to alkaline affinity with low total dissolved solids. D-O isotopes indicate geothermal water is recharged by atmospheric precipitation in the elevation of 5193 - 5247 m. Na-K-Mg equilibrium diagram shows partial equilibrium or mixed water, and the proportion of cold water mixing is 73% to 83%. The temperature range of shallow and deep geothermal reservoir is from 96.85 ℃ to 119.57 ℃ and from 120 ℃ to 200 ℃, respectively. Geothermal water is heated by melting crust and controlled by deep faults. For major construction projects in the Woka Graben, detailed investigation and demonstration should be carried out to avoid the geothermal water channel as much as possible, or to divert the geothermal water and arrange the construction sequence in a reasonable way to overcome the problem.